High-Risk Intracranial Atherosclerotic Stenosis Despite Aggressive Medical Treatment: Protocol for a Prospective Nested Case-Control Study - Wang, Tao; Luo, Jichang; Liu, Changyi; Yang, Bin; Xu, Ran; Li, Long; Yang, Kun; Zhang, Chao; Wang, Yabing; Chen, Yanfei; Gao, Peng; Chen, Jian; et al. (Frontiers in Neurology, 2022)
Introduction Intracranial atherosclerotic disease (ICAD) is one of the most important etiologies of ischemic stroke, especially in Asia. Although medical treatment was recommended as the first-line therapy for ICAD, the recurrent stroke rate was still high in severe stenosis of ICAD despite aggressive medical treatment. Traditionally, the degree of luminal stenosis is used as the principal index for stroke risk stratification in patients with ICAD, while recent evidence suggested that symptomatic atherosclerotic plaques were characterized by plaque features and hemodynamics. This prospective, longitudinal, and nested case-control study aims to identify multimodal imaging predictors of high-risk patients with ICAD refractory to medical treatment and explore a refined risk stratification model based on the above multimodal imaging predictors. Methods This prospective, longitudinal, and nested case-control study includes 400 symptomatic patients with ICAD with 50–99% of stenosis treated with aggressive medical therapy. All patients who meet the eligibility criteria are assessed by multimodal imaging examination from three aspects, including lumen stenosis, plaque characteristics, and hemodynamic features. The enrolled patients receive aggressive medical management, including antiplatelet therapy and cardiovascular risk control. The primary outcome is ischemic stroke or death attributable to the lesion of the target vessel within 1 year. The secondary endpoints are (1) any stroke or death; (2) all-cause mortality; (3) any stroke out of the territory of the responsible lesion; (4) functional outcome with the modified Rankin Scale (mRS). Ethics and Dissemination This study has been approved by the ethics committee of our center ([2021]083) and has been prospectively registered (Registration No: ChiCTR2100048832). Study findings will be disseminated through peer-reviewed publications and presentations at scientific meetings.